Misogyny in Health Professions? An Analysis of the Dalhousie Dentistry Scandal - Hunter, Kelly; Maxwell, Erika; Brunger, Fern (BioéthiqueOnline, 2015)
This commentary offers an explanation for how and why the Dalhousie Dentistry scandal could occur in a society and time where traditional gender roles are seemingly being eradicated. We use Foucault’s modes of objectification, applied to an analysis of the use of “manhood acts” and in relation to the hidden curriculum, to argue that when women threaten the authority of men in health professions, men may subconsciously look for ways to re-exert an unequal and gendered subject-object binary.